2022
DOI: 10.3390/jof8010082
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Organic and Residual Fractions of Nematicidal Culture Filtrates from Thirteen Tropical Trichoderma Strains and Metabolic Profiles of Most-Active

Abstract: The nematicidal properties of Trichoderma species have potential for developing safer biocontrol agents. In the present study, 13 native Trichoderma strains from T. citrinoviride, T. ghanense (2 strains), T. harzianum (4), T. koningiopsis, T. simmonsii, and T. virens (4) with nematicidal activity were selected and cultured in potato dextrose broth to obtain a culture filtrate (CF) for each. Each CF was partitioned with ethyl acetate to obtain organic (EA) and residual filtrate (RF) fractions, which were then t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…Estos resultados sugieren que los consorcios de microorganismos evaluados, HMA, HMA + Trichoderma spp., establecieron interacciones positivas que limitaron el parasitismo del nematodo como ocurrió en cultivos de Cicer arietinum L., Ocidium bacilicum L. inoculados con consorcios de HMA, Trichoderma spp., Bacillus spp., que tuvieron reducciones de M. incognita del 46.00 al 95.00% (Rizvi et al 2018, Tiwari et al 2021). Varios modos de acción están implicados en el control de nematodos: competencia entre HMA y J2 para ocupar sitios en la raíz y por fuentes carbonados, activación de mecanismos de defensa de la planta asociados con la activación de genes que codifican quitinasas, implicadas en la desintoxicación de especies reactivas de oxígeno, que se producen durante la hipertrofia y muerte celular inducida por nematodos al parasitar raíces, como la glutation S-transferasa o la superóxido dismutasa, fitoalexinas, involucradas en la biosíntesis de la lignina, precursora de metabolitos secundarios aromáticos que afectan la viabilidad de huevos y movilidad de J2 (Poveda et al 2020, Moo-Koh et al 2022.…”
Section: Resultados Y Discusiónunclassified
“…Estos resultados sugieren que los consorcios de microorganismos evaluados, HMA, HMA + Trichoderma spp., establecieron interacciones positivas que limitaron el parasitismo del nematodo como ocurrió en cultivos de Cicer arietinum L., Ocidium bacilicum L. inoculados con consorcios de HMA, Trichoderma spp., Bacillus spp., que tuvieron reducciones de M. incognita del 46.00 al 95.00% (Rizvi et al 2018, Tiwari et al 2021). Varios modos de acción están implicados en el control de nematodos: competencia entre HMA y J2 para ocupar sitios en la raíz y por fuentes carbonados, activación de mecanismos de defensa de la planta asociados con la activación de genes que codifican quitinasas, implicadas en la desintoxicación de especies reactivas de oxígeno, que se producen durante la hipertrofia y muerte celular inducida por nematodos al parasitar raíces, como la glutation S-transferasa o la superóxido dismutasa, fitoalexinas, involucradas en la biosíntesis de la lignina, precursora de metabolitos secundarios aromáticos que afectan la viabilidad de huevos y movilidad de J2 (Poveda et al 2020, Moo-Koh et al 2022.…”
Section: Resultados Y Discusiónunclassified
“…Trichoderma mycelium penetrates the eggshell or cuticle of larvae and adults of nematodes, colonizes, absorbs nutrients from nematodes, and causes nematode death ( Marraschi et al, 2019 ). Trichoderma mycoparasitic nematode processes involve the production and co-secretion of various degrading enzymes ( Moo-Koh et al, 2022 ). The induction of Trichoderma activities of β-1, 3-glucanase, chitinase, and protease are increased, which can enhance the immunity of plants to nematodes ( Poveda et al, 2020 ).…”
Section: Application and Mechanism Of Action Of Trichoderma...mentioning
confidence: 99%
“…Trichoderma can inhibit the growth and reproduction of nematodes by secreting antagonistic substances ( Moo-Koh et al, 2022 ). Trichoderma produces a variety of secondary metabolites, including trichomycin, gliotoxin, viridin, antibacterial peptide, β-1, 3-glucanase, chitinase, polypeptides, polyketones, butyrolactones, sesquiterpene heptadecarboxylic acid, terpenes, and some volatile substances (hydrocarbons, alcohols, furans, aldehydes, alkanes, olefins, esters, aromatic compounds, heterocyclic compounds, and various terpenoids) ( Kappel et al, 2020 ).…”
Section: Application and Mechanism Of Action Of Trichoderma...mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that fermentation of Trichoderma longibrachiatum T6 could exert antifungal effects on the pathogen V. mali of apple Valsa canker, such as inhibiting conidia germination, altering mycelial morphology, and blocking growth ( Zhu et al, 2022 ). Research involving an assay targeting Rhizoctonia solani and nematode mortality has demonstrated that the suppression of these pathogens can be attributed to the antibiosis mechanism of Trichoderma virens metabolites ( Halifu et al, 2020 ; Moo-Koh et al, 2022 ). These metabolites functioned as inhibitors, facilitating the penetration of Trichoderma hyphae into prey fungi and hampering vital processes such as cell wall synthesis, growth, reproduction, sporulation, nutrient uptake, metabolite production in target pathogens, and induction of defense system ( Halifu et al, 2020 ; Gan et al, 2022 ; Zhu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%